2019
DOI: 10.1111/nph.16140
|View full text |Cite
|
Sign up to set email alerts
|

A new wrinkle in our understanding of the role played by auxin in root gravitropism

Abstract: This article is a Commentary on Zhang et al., 224: 761–774.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These included a QTL on chromosome 4 that was 33 kb distant from a gene model for an auxin transporter component. Recent research has shown that auxin can upregulate genes for starch synthesis (Su & Masson, 2019). A third starch QTL was located on chromosome 5 within 7 kb to a guanosine diphosphate‐mannose transporter gene model.…”
Section: Discussionmentioning
confidence: 99%
“…These included a QTL on chromosome 4 that was 33 kb distant from a gene model for an auxin transporter component. Recent research has shown that auxin can upregulate genes for starch synthesis (Su & Masson, 2019). A third starch QTL was located on chromosome 5 within 7 kb to a guanosine diphosphate‐mannose transporter gene model.…”
Section: Discussionmentioning
confidence: 99%